Islam and Democracy : Compatibility and Challenges in Muslim-Majority Countries - Nazhwa Rusvianda Ahmad; Nazma Nurfadilah Alyudin; Oktaviani Rizqi Wahyuningtyas; Refnie Afnisa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The relationship between Islam and democracy has been a complex and often debated topic, particularly in Muslim-majority countries. This research aims to explore the compatibility between Islamic principles and democratic values using Indonesia as a case study. As one of the largest Muslim countries in the world, Indonesia offers a unique context in integrating religious teachings with the modern democratic system. Through qualitative methods that included a Google Form-based survey and a literature review of academic articles and journals, this research found that the majority of respondents (70%) believe that democratic values are in line with Islamic teachings, such as justice, deliberation and equality. However, the research also identified a number of challenges that Indonesia faces in harmonizing the two concepts. The main challenges include differences in the interpretation of Islamic law, difficulties in balancing sharia law with secular law, and the issue of political pluralism. In addition, factors such as intolerance, radicalism and identity politics often become obstacles in creating harmony between religious and democratic values. Despite these obstacles, Indonesia has made significant progress through moderation, strengthening civil society, and successfully managing religious and cultural diversity. Local traditions such as deliberation, gotong royong and pluralism provide a strong foundation for building an inclusive democratic system. This approach is not only relevant for the Indonesian context, but can also serve as a model for other Muslim-majority countries seeking to integrate religion and democracy. This research offers a new contribution to the understanding of the dynamics of the relationship between Islam and democracy, and highlights the importance of civil society strengthening, pluralism education, and the adaptation of religious values in the context of modern democracy. With the results obtained, this research is expected to be a reference for other Muslim countries in creating harmonious and sustainable political governance.